Tournament Behavior in Hedge Funds: High-water Marks, Fund Liquidation, and Managerial Stake - Aragon, George O.; Nanda, Vikram (Review of Financial Studies, 2012)
We analyze whether risk shifting by a hedge fund manager is related to the manager's incentive contract, personal capital stake, and the risk of fund closure. We find that the propensity to increase risk following poor performance is significantly weaker when incentive pay is tied to the fund's high-water mark and when funds face little immediate risk of liquidation. Risk shifting is also less prevalent when a manager has a significant amount of personal capital invested in the fund. Overall, high-water mark provisions, managerial stake, and low risk of fund closure appear to make a hedge fund manager more conservative with regard to risk shifting. The Author 2011. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.